2023
DOI: 10.1021/acs.jafc.2c08704
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, Formation Kinetics and Core Composition of Pea and Soy 7S and 11S Globulin Amyloid Fibrils

Abstract: Legume seed storage proteins can be induced to form amyloid fibrils upon heating at low pH, which could improve their functionality for use in food and materials. However, the amyloidogenic regions of legume proteins are largely unknown. Here, we used LC-MS/MS to determine the amyloid core regions of fibrils formed by enriched pea and soy 7S and 11S globulins at pH 2, 80 °C, and characterized their hydrolysis, assembly kinetics, and morphology. A lag phase was absent from the fibrillation kinetics of pea and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…For example, Zhang et al demonstrated that acid hydrolysis of 7S and 11S proteins from peas and soybeans could facilitate their self-assembly to form protofibril structures, where the 7S protein hydrolysate self-assembled to form fibers faster than that of the 11S globulin, which is mainly attributed to the higher content of acidic amino acid residues in β-conglycinin. Nevertheless, regions with highly charged and hydrophilic groups were rarely involved in forming protofibrils . Furthermore, it has been demonstrated that enzymatic hydrolysis of sodium caseinate liberated negatively charged peptides that tightly enclosed the surface of the hydrophobic moieties, allowing the peptides to self-assemble into more compact structures …”
Section: Stimulus-responsive Self-assembly Of Fpdmpsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Zhang et al demonstrated that acid hydrolysis of 7S and 11S proteins from peas and soybeans could facilitate their self-assembly to form protofibril structures, where the 7S protein hydrolysate self-assembled to form fibers faster than that of the 11S globulin, which is mainly attributed to the higher content of acidic amino acid residues in β-conglycinin. Nevertheless, regions with highly charged and hydrophilic groups were rarely involved in forming protofibrils . Furthermore, it has been demonstrated that enzymatic hydrolysis of sodium caseinate liberated negatively charged peptides that tightly enclosed the surface of the hydrophobic moieties, allowing the peptides to self-assemble into more compact structures …”
Section: Stimulus-responsive Self-assembly Of Fpdmpsmentioning
confidence: 99%
“…Nevertheless, regions with highly charged and hydrophilic groups were rarely involved in forming protofibrils. 59 Furthermore, it has been demonstrated that enzymatic hydrolysis of sodium caseinate liberated negatively charged peptides that tightly enclosed the surface of the hydrophobic moieties, allowing the peptides to self-assemble into more compact structures. 22 The hydrophilicity/hydrophobicity and secondary structure elements (such as α-helices or β-sheets) also considerably affect the peptides' self-assembly behavior.…”
Section: Internal Structural Stimulusmentioning
confidence: 99%
“…This result was in good agreement with that of Zhang and Dee. 23 Since ThT and natural Cur fluorescence emission might interfere, SPIA@Cur formation kinetics were recorded using only the Cur fluorescence signal. The lag time for SPIA@Cur formation was shortened (≈160 min), and the apparent aggregation constant rate was increased significantly.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…3 It is documented that PNF formation from SPI occurs mainly through hydrophobic interactions, while charged and hydrophilic residues have rarely been observed in those regions that participate in PNF formation. 23 In addition to self-assembly and PNF formation, the production of soybean-based protein fibers is now being explored to produce solution-blown spinning fibers with the help of other copolymers. 24 Curcumin (Cur) is the major natural polyphenolic compound of turmeric (Curcuma longa) rhizomes.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation